2018
DOI: 10.1002/acp.3504
|View full text |Cite
|
Sign up to set email alerts
|

Intoxicated eyewitnesses: The effect of a fully balanced placebo design on event memory and metacognitive control

Abstract: Few studies have examined the impact of alcohol on metacognition for witnessed events. We used a 2 × 2 balanced placebo design, where mock witnesses expected and drank alcohol, did not expect but drank alcohol, did not expect nor drank alcohol, or expected but did not drink alcohol. Participants watched a mock crime in a bar-lab, followed by free recall and a cued-recall test with or without the option to reply "don't know" (DK). Intoxicated mock witnesses' free recall was less complete but not less accurate. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 58 publications
(111 reference statements)
0
17
0
Order By: Relevance
“…The adapted AMT is an extension of the original AMT, whereby, due to the tendencies of intoxicated individuals to focus on salient and to neglect peripheral details, overall fewer details are recalled. Both Altman et al () and Gawrylowicz et al () reported results in line with the adapted AMT. However, the findings of Flowe et al () did not support the adapted AMT and suggested that intoxicated individuals were able to process both salient and peripheral cues as well as individuals who were not intoxicated.…”
Section: Four Mechanismsmentioning
confidence: 71%
See 4 more Smart Citations
“…The adapted AMT is an extension of the original AMT, whereby, due to the tendencies of intoxicated individuals to focus on salient and to neglect peripheral details, overall fewer details are recalled. Both Altman et al () and Gawrylowicz et al () reported results in line with the adapted AMT. However, the findings of Flowe et al () did not support the adapted AMT and suggested that intoxicated individuals were able to process both salient and peripheral cues as well as individuals who were not intoxicated.…”
Section: Four Mechanismsmentioning
confidence: 71%
“…Whereas many studies have included a placebo condition in which participants only thought that they were intoxicated but actually had not received any alcohol (i.e., placebo), no study had until now included a condition in which participants did not think that they were intoxicated but actually had received some alcohol (i.e., reverse placebo). Gawrylowicz et al () addressed this issue and conducted a study with a fully balanced placebo design, in which participants watched a mock crime in a bar lab. They found that although drinking alcohol (BAC 0.06%), both knowingly or unknowingly, affected the number of correct details that the participants freely recalled, it did not affect the accuracy rate on the free‐recall task, because they did not provide more incorrect details.…”
Section: Experimental Studiesmentioning
confidence: 99%
See 3 more Smart Citations